IGF1 and NRG1 Enhance Proliferation, Metabolic Maturity, and the Force-Frequency Response in hESC-Derived Engineered Cardiac Tissues - Cassady E. Rupert; Kareen L. K. Coulombe (Hindawi Limited, 2017)
Insulin-like growth factor 1 (IGF1) and neuregulin-1β (NRG1) play important roles during cardiac development both individually and synergistically. In this study, we analyze how 3D cardiac tissue engineered from human embryonic stem cell- (hESC-) derived cardiomyocytes and 2D-plated hESC-cardiomyocytes respond to developmentally relevant growth factors both to stimulate maturity and to characterize the therapeutic potential of IGF1 and NRG1. When administered to engineered cardiac tissues, a significant decrease in active force production of ~65% was measured in all treatment groups, likely due to changes in cellular physiology. Developmentally related processes were identified in engineered tissues as IGF1 increased hESC-cardiomyocyte proliferation 3-fold over untreated controls and NRG1 stimulated oxidative phosphorylation and promoted a positive force-frequency relationship in tissues up to 3 Hz. hESC-cardiomyocyte area increased significantly with NRG1 and IGF1 + NRG1 treatment in 2D culture and gene expression data suggested increased cardiac contractile components in engineered tissues, indicating the need for functional analysis in a 3D platform to accurately characterize engineered cardiac tissue response to biochemical stimulation. This study demonstrates the therapeutic potential of IGF1 for boosting proliferation and NRG1 for promoting metabolic and contractile maturation in engineered human cardiac tissue.